Politics of scarcity: resource conflicts in international relations - Connelly, Philip (O.U.P. LondonGB, 1975)
Provides an overview of the nature of resources and the special problem of energy, and the economic mechanisms with which they are associated. Identifies the situation and objectives of the following - the resource importing industrial nations; the resource self-sufficient nations; and the resource-poor developing nations. Discusses the implications for economic and political policies of the interaction of the interests of these main actors in the resource arena.